XI A study in power - Brown, Kerry (London Icon Books Ltd, 2022)
Although Xi Jinping came to power a decade ago, he remains an enigmatic figure in the West. His priority has always been to keep China as stable as possible, steering a course through a period if astounding economic growth, while ensuring that nothing challenges the political status quo. But with unrest in Hong Kong, reports of human rights abuses in Xinjiang, and the outbreak of a virus that would change the world, suddenly understanding Xi's China is more important that ever before.
Includes Bibliographical reference and index